2018
DOI: 10.1111/ejn.14097
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive threshold hunting reveals differences in interhemispheric inhibition between young and older adults

Abstract: Interhemispheric inhibition between bilateral motor cortices is important for the performance of unimanual activities and may be compromised with advancing age. Conventionally, interhemispheric inhibition is assessed using paired-pulse transcranial magnetic stimulation (TMS) with constant conditioning and test stimulation parameters. Adaptive threshold hunting TMS, whereby a target motor-evoked potential amplitude is maintained in the presence of the conditioning, may provide an alternative means of assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
(78 reference statements)
1
6
0
Order By: Relevance
“…It should be noted that the behavioral associations of S-IHI active were only found in the young group. The present results showed no apparent difference of IHI between the two groups—at least partly in line with the previous studies for S-IHI (Hinder et al 2010 ; Hermans et al 2018 ) but for L-IHI (Mooney et al 2018 )—despite the behavioral differences. The first possible explanation for the lack of behavioral associations in the older group could be that the amount of mirror activity and the performance of anti-phase tapping in older adults are rather associated with neural circuits other than the one represented by S-IHI active .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It should be noted that the behavioral associations of S-IHI active were only found in the young group. The present results showed no apparent difference of IHI between the two groups—at least partly in line with the previous studies for S-IHI (Hinder et al 2010 ; Hermans et al 2018 ) but for L-IHI (Mooney et al 2018 )—despite the behavioral differences. The first possible explanation for the lack of behavioral associations in the older group could be that the amount of mirror activity and the performance of anti-phase tapping in older adults are rather associated with neural circuits other than the one represented by S-IHI active .…”
Section: Discussionsupporting
confidence: 93%
“…The CS was delivered to the left primary motor cortex and the TS was delivered to the right primary motor cortex to measure IHI from the left to the right primary motor cortex. This direction was chosen based on the previous studies examining IHI from the active to the resting primary cortex in older adults (Talelli et al 2008 ; Hinder et al 2010 ; Mooney et al 2018 ; Ermer et al 2020 ). Two ISIs were adopted to assess IHI: 10 ms for S-IHI and 40 ms for L-IHI (Chen et al 2003 ; Ni et al 2009 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, although generally believed to have a dampening effect on cortical excitability (Nitsche and Paulus, 2000), cathodal tDCS has been shown to enhance motion perception in a visual tracking task (Antal et al, 2004), possibly interacting with a reduced signal-to-noise ratio in neural processing in the OA group (Hämmerer et al, 2013). Future studies should also investigate the effect of a bilateral S1 electrode setup (Fujimoto et al, 2014) specifically in OA, since it might interfere stronger with age-related interhemispheric activation changes (Mooney et al, 2018; Strauss et al, 2019). It is also possible that afferent sensory functions are modulated in a different way by means of classical tDCS protocols as compared to efferent motor functions.…”
Section: Discussionmentioning
confidence: 99%
“…IHI is most pronounced at ISIs of 8-10 ms and 40-50 ms, which are referred to as short and long latency IHI, respectively (SIHI and LIHI). Most studies, but not all [119,120], testing IHI at rest, revealed that both SIHI [121,122] and LIHI [123][124][125] did not differ between older and young subjects. By contrast, there is evidence that elderly subjects have less lateralized cortical activation during various motor tasks, including hand grip [126].…”
Section: Tms Studiesmentioning
confidence: 91%